2013
DOI: 10.1162/jocn_a_00345
|View full text |Cite
|
Sign up to set email alerts
|

Seeing It My Way or Your Way: Frontoparietal Brain Areas Sustain Viewpoint-independent Perspective Selection Processes

Abstract: A hallmark of human social interaction is the ability to consider other people's mental states, such as what they see, believe, or desire. Prior neuroimaging research has predominantly investigated the neural mechanisms involved in computing one's own or another person's perspective and largely ignored the question of perspective selection. That is, which brain regions are engaged in the process of selecting between self and other perspectives? To address this question, the current fMRI study used a behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
127
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(145 citation statements)
references
References 68 publications
14
127
1
3
Order By: Relevance
“…However, presenting self-and other-belief trials intermixed might have biased the participants to take the other's perspective which resulted in this pattern of reaction times. This is also consistent with findings from visual perspective taking, which previously revealed faster reaction times for judging the other's compared to one's own perspective in a task in which subjects were asked for both perspectives in an interleaved fashion [50,54].…”
Section: Discussionsupporting
confidence: 89%
“…However, presenting self-and other-belief trials intermixed might have biased the participants to take the other's perspective which resulted in this pattern of reaction times. This is also consistent with findings from visual perspective taking, which previously revealed faster reaction times for judging the other's compared to one's own perspective in a task in which subjects were asked for both perspectives in an interleaved fashion [50,54].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, in the present study, using an implicit belief attribution task that is analogous to earlier used explicit ToM task, we found an activation of the MPFC in the true belief - object present condition, but not in the false belief conditions. Earlier studies have found that the MPFC is involved in representing various characteristics of other agents besides their beliefs, such as their appearance and emotions [27], [28] or a viewpoint-independent perspective selection [15].…”
Section: Discussionmentioning
confidence: 99%
“…McCleery et al used ToM tasks in which participants solved high-level visuo-spatial conflicts between their own and others' perspective. It may be put forward that computing the others' perspective in the left TPJ was necessary to, then, decouple one's from other's perspective in the right dlPFC and solve the conflict of perspectives (see also Vogeley et al, 2001;Ramsey et al, 2013). Our tasks did not require high-level computation of differences in perspective and have probably rather induced perspective inhibition.…”
Section: Modulations Of the Mns Nodes Activation Between Empathy And mentioning
confidence: 99%